2020
DOI: 10.1111/mec.15613
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of plant defensive glucosinolates by an herbivorous caterpillar is beneficial to its endoparasitic wasp

Abstract: Multitrophic interactions involving plants, insect herbivores, and their antagonists are ubiquitous in terrestrial ecosystems and underpin our understanding of the structure and function of ecological communities (Stam et al., 2014). Most plants in nature are attacked by insect herbivores, and high infestations can severely damage plant tissues and thus reduce plant fitness (Johnson, Lajeunesse, & Agrawal, 2006). To prevent or reduce attack, plants employ an array of strategies to reduce herbivory, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…Here, larvae feeding on cabbage, which produces the aliphatic methylsulfoxide-containing 3msob-GSL ( Figure 1 ), strongly depleted cysteine for use in GSH biosynthesis and resulted in an imbalanced protein metabolism ( Figure 2 ) and thus slower larval growth, in agreement with our previous findings [ 12 ]. Interestingly, this effect was also found in parasitoids of Plutella xylostella larvae that were raised on GSL-rich A. thaliana Col-0 [ 26 ]. A recent study, in which H. armigera larvae were fed with sinigrin (allyl GSL), confirms that protein metabolism is disturbed in GSL-fed larvae, with upregulations in transcripts related to glutathione and amino acid metabolism [ 27 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Here, larvae feeding on cabbage, which produces the aliphatic methylsulfoxide-containing 3msob-GSL ( Figure 1 ), strongly depleted cysteine for use in GSH biosynthesis and resulted in an imbalanced protein metabolism ( Figure 2 ) and thus slower larval growth, in agreement with our previous findings [ 12 ]. Interestingly, this effect was also found in parasitoids of Plutella xylostella larvae that were raised on GSL-rich A. thaliana Col-0 [ 26 ]. A recent study, in which H. armigera larvae were fed with sinigrin (allyl GSL), confirms that protein metabolism is disturbed in GSL-fed larvae, with upregulations in transcripts related to glutathione and amino acid metabolism [ 27 ].…”
Section: Discussionmentioning
confidence: 83%
“…Again, this effect was stronger for individuals on the cabbage diet (containing the aliphatic 3msop-GSL), and delays in pupations have previously been seen in S. littoralis larvae raised on A. thaliana Col-0, which contains largely methylsulfoxide-aliphatic GSLs like 4msob and 3msop, among others [ 29 ]. Similarly, parasitoids developing on P. xylostella larvae that fed on 4msob-ITC-infused leaves suffered from delayed development, lower adult emergence success, and lower body fat content [ 26 ] further indicating that GSL-derived compounds affect general animal metabolism, and that these effects are not unique to lepidopteran herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in some cases that such compounds can move up the food chain and affect not only the consuming pest herbivores, but subsequently also herbivore natural enemies (Gauld et al 1992;Hartmann 2004;Harvey et al 2003;Petschenka and Agrawal 2016), with potential unintended effects for plant protection. In Brassicales plants more specifically, plant-produced glucosinolates have been shown to influence predators (Sporer et al 2020;Sun et al 2019) and parasitoids (Sun et al 2020) of herbivores. Cabbage aphid predators, such as C. carnea, can suffer significantly from ingesting insects containing glucosinolates.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolization of plant defense metabolites is considered central for the ability of species to overcome chemical defenses of their host plants ( Heckel, 2014 ), and recent papers have established direct molecular evidence for this concept ( Sun et al, 2019 ; Sun et al, 2020 ; Poreddy et al, 2015 ). A major metabolization product of TA-G is TA-Cys, with about 25% of the ingested TA-G accumulating in this form.…”
Section: Discussionmentioning
confidence: 99%
“…Insect herbivores commonly metabolize defense metabolites, with important consequences for the toxicity of the compounds ( Heckel, 2014 ; Pentzold et al, 2014 ). Recent studies identified a series of enzymes that metabolize plant defense metabolites and thereby benefit herbivore growth and fitness ( Sun et al, 2019 ; Sun et al, 2020 ; Poreddy et al, 2015 ). However, to date, the behavioral consequences of insect metabolism of plant defense metabolites are little understood, despite the importance of behavioral effects of plant defenses for plant fitness and evolution in nature ( Mithöfer and Boland, 2012 ; Huber et al, 2016a ; Huber et al, 2016b ; War et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%